Board expertise and Islamic bank performance in a two-tier system - Ferdy Putra (Journal of Islamic Accounting and Finance Research, 2025)
Purpose - The purpose of this study is to analyze the influence of the expertise of the directors, board of commissioners, and sharia supervisory board on the performance of Islamic banking. Method - This study uses three areas of expertise, namely accounting/finance, business, and sharia expertise. The sample of this study is Islamic banking from 2014 to 2024, which meets the research criteria. Result - This study found that the expertise of the directors, board of commissioners, and sharia supervisory board improves the performance of Islamic banking. Implication - This study provides implications for companies and regulators to encourage and develop regulations that require the composition of the directors, board of commissioners, and sharia supervisory board with accounting/finance, business, and sharia expertise. Originality - As far as the author knows, research on board expertise in Islamic banking in countries that adopt a two-tier system has never been conducted.